Reverse Total Shoulder Arthroplasty as Treatment for Rotator Cuff-Tear Arthropathy and Shoulder Dislocations in an Elderly Male with Parkinson’s Disease - John G. Skedros; James S. Smith; Tanner D. Langston; Micheal G. Adondakis (Case Reports in Orthopedics)
We report the case of a 70-year-old male with Parkinson’s disease (PD) and recurrent traumatic left shoulder dislocations. This case is rare because (1) he had a massive irreparable rotator cuff tear and end-stage arthritis (i.e., rotator cuff-tear arthropathy) of the same shoulder and (2) his shoulder was ultimately reconstructed with a reverse total shoulder arthroplasty (RTSA). His first dislocation occurred after a fall. Recurrent shoulder dislocations occurred despite successful closed reduction and physical therapy. Initial surgical treatment included an open capsular-labral reconstruction; RTSA was not an ideal option because of the presumed risk of failure from PD-related dyskinesias. However, the capsular-labral reconstruction failed after he lost balance and stumbled but did not fall. A RTSA was then done which restored the patient’s shoulder stability and greatly improved his pain. At final follow-up two years later, he reported pain relief and improved function. This was partially attributed to the fact that he had moved to an assisted living center. He also began using an electric wheelchair one year after the RTSA. We report this case because of the unusual set of conditions and circumstances, namely, the implantation of a RTSA in a patient with PD and shoulder instability.